2014
DOI: 10.1186/1476-511x-13-138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thymus hirtus sp. algeriensis Boiss. et Reut. (Lamiaceae) essential oil on healing gastric ulcers according to sex

Abstract: BackgroundThymus algeriensis Boiss. et Reut. (Lamiaceae), popularly known as “mougecha” or “mazoukcha” is prolific in Mediterranean regions, mostly in North Africa, and is used in folk medicine to treat of stomach diseases.MethodsIn this study, animals were induced with gastric ulcers using HCl/ethanol (0.3 M HCl/60% ethanol) and treated orally with essential oil of Thymus algeriensis (EOTa) in various doses ranging from 54 mg/kg body weight to 180 mg/kg body weight.ResultThe dose found to be effective was 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
(39 reference statements)
3
31
1
Order By: Relevance
“…On the fourth day, 70% ethanol was given orally to each animal in groups III, IV and V at 10 ml/kg to induce gastric ulceration [24]. The animals in the fourth group were administered omeprazole, a proton pump inhibitor, orally 1 h before ethanol administration at a dose of 20 mg/kg [25]. Omeprazole was used as a reference anti-ulcer drug.…”
Section: Experimental Designmentioning
confidence: 99%
“…On the fourth day, 70% ethanol was given orally to each animal in groups III, IV and V at 10 ml/kg to induce gastric ulceration [24]. The animals in the fourth group were administered omeprazole, a proton pump inhibitor, orally 1 h before ethanol administration at a dose of 20 mg/kg [25]. Omeprazole was used as a reference anti-ulcer drug.…”
Section: Experimental Designmentioning
confidence: 99%
“…n-butanol fraction of crude aqueous leaf extract of T. Serrulatus is composed of alkaloids, saponins, polyphenols, tannins and phytosterols which was comparable with the secondary metabolites of hexane, ethyl acetate, chloroform, butanol and methanol leaves extracts of T. vulgaris [33]. Aqueous and 80% methanol crude extract of T. schimperi leaves was qualitatively analyzed and the presence of steroids, alkaloids, flavonoids, saponins and tannins has been detected [34]. The other report showed that the wild Abyssinian thyme aerial parts the flower had highest total phenolic content (0.5 µg/ml) and the leaf the lowest and the whole thyme plant had the highest condensed tannin content (0.9 µg/ml).…”
Section: Phytochemistry Of Thymus Schimperi and Thymus Serrulatusmentioning
confidence: 87%
“…Aqueous and methanol 80% extract of T. schimperi showed a reduction in blood glucose levels in a dose-and time-dependent manner. T. schimperi aqueous extracts of 250 and 500 mg/kg showed reduction of 22.65% and 33.15% in plasma glucose levels, respectively after 4 h of extract administration and In case of 80% methanol extraction at 250 and 500 mg/kg showed reduction of 30.06% and 38.35% in plasma glucose levels, respectively [34]. The oral administration of aqueous extract of T. schimperi leaves and its essential oil distillate at doses of (250, 500, 750 and 1000 mg/kg) and (1 and 1.5 ml/kg) was respectively evaluated for J Clin Exp Pharmacol, Vol.…”
Section: Efficacy Of T Schimperi and T Serrulatusmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar observations were found by Guesmi et al using essential oil of Thymys algeriensis in the treatment of gastric ulcer induced by HCl/ ethanol. 74) In this study, we conclude that the oral administration of the essential oil of Juniperus phoenicea has potent anti-ulcer activity, which justifies the ethnomedical claims about its significant gastroprotective effect, as evaluated by the significant antioxidant activity because it reduces the MDA level and increases the GSH, GST, GPx, CAT and SOD levels. This effect may be related to an increase in the gastric mucosal defence mechanisms.…”
Section: )mentioning
confidence: 89%